2013
DOI: 10.1103/physrevb.87.165142
|View full text |Cite
|
Sign up to set email alerts
|

Strong coupling expansion in a correlated three-dimensional topological insulator

Abstract: Motivated by recent studies which show that topological phases may emerge in strongly correlated electron systems, we theoretically study the strong electron correlation effect in a three-dimensional topological insulator, where the effective Hamiltonian can be described by the Wilson fermions. We adopt a 1/r long-range Coulomb interaction as the interaction between the bulk electrons. Based on the U(1) lattice gauge theory, the strong coupling expansion is applied by assuming that the effective interaction is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…The role of Coulomb interaction depends crucially on the fermion dispersion and the dimension. Extensive renormalization group (RG) analysis [53] have revealed that Coulomb interaction is marginally irrelevant in 2D Dirac semimetal [5,36,37], 3D Dirac/Weyl semimetal [38][39][40][41], and also 3D double Weyl semimetal [49,50]. The Fermi liquid (FL) theory is valid in 2D Dirac semimetal [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Coulomb interaction depends crucially on the fermion dispersion and the dimension. Extensive renormalization group (RG) analysis [53] have revealed that Coulomb interaction is marginally irrelevant in 2D Dirac semimetal [5,36,37], 3D Dirac/Weyl semimetal [38][39][40][41], and also 3D double Weyl semimetal [49,50]. The Fermi liquid (FL) theory is valid in 2D Dirac semimetal [5].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of long-range Coulomb interaction have been studied in various types of semimetals [5,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The role of Coulomb interaction depends crucially on the fermion dispersion and the dimension.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we follow [17,[43][44][45][46][47][48][49] and use the WilsonDirac Hamiltonian as the simplest realistic lattice model of Dirac semimetals and/or topological insulators, which are then tuned into a Weyl semimetal phase by adding the parity-or time-reversal-breaking terms. In our case, parity is broken by the chiral chemical potential µ A .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we find a new phase with an in-plane antiferromagnetism in 2D, which appears by the similar mechanism as that of the pion condensate phase (so-called "Aoki phase") in lattice QCD with Wilson fermion [9]. On the other hand, such a phase does not appear in 3D, and the electron correlation results in the shifting of the topological phase boundary [10].…”
Section: Introductionmentioning
confidence: 77%
“…[10] for the details of calculation). Here we should note that φ π vanishes even in the strong coupling limit β = 0, unlike in the 2D case, since the momentum integral at the one-loop level converges in (3 + 1)-dimensions.…”
Section: Pos(lattice 2013)050mentioning
confidence: 99%